Transforming Indian Agriculture through Agripreneurs - Kular, Inderpreet Kaur; Brar, Amanpreet Singh (Indian Journal of Marketing, 2012)
India is the third largest producer of agricultural commodities in the world. Agriculture is the backbone of the Indian economy. The Indian economy is growing at more than eight per cent for the past several years, but growth rate of agriculture has been stagnant at around 2 per cent. Over two-thirds of the country’s population is directly dependent upon agriculture, thus, the slow growth rate of the agrarian economy affects the lives of about 700 million people, some of them are deprived of even the basic amenities. The contribution of agriculture to economy’s GDP declined from 49 per cent in 1951 to 36 per cent in 1981 to only 18 per cent in 2007-08, which means that the relative fast growth rate of other sectors added to the income of urban population and raises the prices of commodities and real estate and indirectly pushes the rural population towards poverty. Thus, there is a need to increase the income of the farmers from a unit of holding, which is constantly declining due to the division of holding with the growth in population and rising demand of land for industrial residential sectors due to the growth of economy at 8 per cent plus growth rate. The income of the farmers can be increased by two ways: (a) Through cultivation of high value crops in place of traditional crops (b) Adding value to the agri-produce through grading, processing and packing. The objective of the present study is to develop a detailed and clear picture about the small and medium agro-processing systems, their requirement to effectively manufacture and market processed products, and to review agro-processing service provision, research and extension linkages. The features and constraints of the agro-industry are examined to assess their potential contributions and challenges. The study was implemented through a review of literature, mainly for commodity-specific agro-processing enterprises. India is the second largest producer of fruits and vegetables in the world. There is an enormous potential to be tapped, which will also be advantageous for both domestic and export markets. The agro-industry of Punjab has an important role to play in the economic development and has a strong potential to meet the local needs and export requirements. The Government should provide with the basic infrastructure required, such as the supply of electricity, roads and communication network. The Government has established the skill training centres for enhancement of the skill development in the farmers, artisans and other users. The industry is facing many challenges such as uncertainty of finances, limited research, limited technical advice and limited marketing information.